Previously unclassified mutation of mtDNA m.3472T>C: Evidence of pathogenicity in Leber’s hereditary optic neuropathy - Sheremet, N. L.; Nevinitsyna, T. A.; Zhorzholadze, N. V.; Ronzina, I. A.; Itkis, Y. S.; Krylova, T. D.; Tsygankova, P. G.; Malakhova, V. A.; Zakharova, E. Y.; Tokarchuk, A. V.; Panteleeva, A. A.; Karger, E. M.; et al. (Biochemistry (Moscow), 2016)
Leber’s hereditary optic neuropathy (LHON) refers to a group of mitochondrial diseases and is characterized by defects of the mitochondrial electron transport chain and decreased level of oxidative phosphorylation. The list of LHON primary mtDNA mutations is regularly updated. In this study, we describe the homoplasmic nucleotide substitution m.3472T>C in the MT-ND1 (NADH-ubiquinone oxidoreductase chain 1) gene and specific changes in cell metabolism in a patient with LHON and his asymptomatic sister. To confirm the presence of mutation-related mitochondrial dysfunction, respiration of skin fibroblasts and platelets from the patient and his sister was studied, as well as the mitochondrial potential and production of reactive oxygen species in the skin fibroblasts. In addition, based on characteristics of the toxic effect of paraquat, a new approach was developed for detecting the functional activity of complex I of the mitochondrial respiratory chain.